Validation of ICTERUS, a Knowledge-based Expert System for Jaundice Diagnosis - Molino, G.; Marzuoli, M.; Molino, F.; Battista, S.; Bar, F.; Torchio, M.; Lavelle, S. M.; Corless, G.; Cappello, N. (Methods of Information in Medicine, 2000)
The study aimed to describe an example of the assessment and validation of knowledge-based clinical expert systems. The paper focuses on ICTERUS, an expert system for jaundice diagnosis. It describes system design, the methodology applied for upgrading and validating the program, and the most important outcomes of the validation procedure. The clinical validation of the system on a very large European database (Euricterus Project) shows that diagnostic conclusions are reliable in about 70% of eligible cases. This figure appears acceptable for a system which provides decision support only on the basis of clinical data, assuming that the final decision is achieved under user responsibility. Expected biases, limitations and inconsistencies in the practical application of the system are discussed.
Keywords: Jaundice; Liver Diseases; Knowledge-based Expert System; System Validation; Diagnostic Accuracy